SLE DALAM KEHAMILAN DISERTAI ABORTUS BERULANG - Primadella Fegita (Nusantara Hasana Journal, 2024)
Systemic Lupus Erythematosus (SLE) is a complex autoimmune disease that attacks various body systems, characterized by the presence of autoantibodies against cells involving many organ systems in the body. 1,2 This disease can be found at all ages, most often found in old age. 21-30 years.1,2. SLE is multifactorial, including genetic, hormonal and environmental factors, especially UV rays. 1 Overall, the death rate for mothers with systemic lupus erythematosus (SLE) increases up to 20 times. SLE during pregnancy increases the risk of complications, such as recurrent miscarriage, premature birth, fetal loss, fetal growth restriction, and hypertension. In addition, the risk of thrombosis, infection, and delivery via cesarean section is also higher in pregnancies with SLE.9 In this case report we will discuss a 34 year old female patient diagnosed with SLE at G5P0A4H0 gravid 19-20 weeks. In this case there is multidisciplinary knowledge in the patient management process so the author is interested in raising this case as a case report.